The socially engaged corporation: Attitudes and knowledge related to collaboration with non-governmental organizations - Marta Karwacka; Karolina Kitzman (Foundations of Management, 2014)
Collaboration between business and non-governmental organizations (NGOs) is a relatively new phenomenon in the Polish market. It appears, however, that corporations recognized as socially responsible in Poland are starting to see greater benefits than before in collaboration with the third sector. More and more often, the collaboration involves an exchange of different resources and not merely sponsorship of specific events or social campaigns. The present study stresses the developmental aspect of the business-NGO collaboration. The collaboration by entities has been analyzed on the basis of recent literature dealing with sustainability management, Corporate Social Responsibility and business- NGO relations, and also on own research. The study discusses the conceptions of socially responsible corporations reaching new markets and customers on the basis of collaboration with NGOs.
Keywords: 650; socially responsible corporation; corporate social objectives; non-governmental organizations; NGO; third sector; business sector; sustainability; NGO resources; benefits of collaboration with the third sector; Bottom of the Pyramid; social innovation; intersectoral relations; intersectoral collaboration; business-NGO alliances